STUDI KOMPARASI AKTIVITAS ANTIOKSIDAN DAUN JERUK PURUT (Citrus hystrix DC) DAN DAUN JERUK NIPIS (Citrus aurantifolia (christm) Swingle) ASAL KOTA TERNATE MENGGUNAKAN METODE PEREDAMAN RADIKAL BEBAS DPPH - Handayani, Virsa; Naid, Tadjuddin; Umasangaji, Ria Fitriani (Fakultas Farmasi UMI, 2020)
Citrus (Citrus hystrix DC) and lime leaves (Citrus aurantifolia (christm) Swingle) are a Rutaceae family which contain flavonoids with antioxidant activity. The aim of this study is to compare the antioxidant activity of the citrus and lime leaves using DPPH free radical suppression method. The extraction of citrus and lime leaves by maceration method using ethanol 96 %. The antioxidant assay qualitatively by Thin Layer Chromatography (TLC) used the eluent n-hexane : ethyl acetat (7:3). The antioxidant assay quantitatively used DPPH free radical suppression method measured the absorption at the wavelength 515 nm. The results showed that the IC50 value of the citrus is 228.695 Âµg/mL. This showed that the potential of the antioxidant activity of the sample is weak; however, the IC50 value of the lime leaves is 335.064 Âµg/mL. this showed that the antioxidant activity of thev sample is not active.